(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
The article highlights the main points of the testimony given by Carmine Schiavone, former Casalesi boss, in 1997 to the Parliamentary Commission on the Waste Cycle and related illegal activities, declassified in 2013. It emerges a picture of the origins of hazardous waste illegal trafficking in Campania, with toxic drums buried in quarries, political and Masonic cover-ups and an increase in cancer cases in the area between the provinces of Naples and Caserta.